2019
DOI: 10.1002/ajhb.23380
|View full text |Cite
|
Sign up to set email alerts
|

The relationship among the age at menarche, anthropometric characteristics, and socio‐economic factors in Bengali girls from Kolkata, India

Abstract: The aim of the study was to measure the causal effect of selected socio-economic factors and anthropometrical characteristics on the menarche occurrence. Methods:The sample consisted of 2195 Bengali girls (aged 7-21) from middleclass families, from Kolkata city, India. The age at menarche was recorded from the retrospective data and status quo method. The causal effect of anthropometric and socio-economic variables on menarche occurrence was estimated by the nonparametrical analysis of survival probability (su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 59 publications
3
19
0
3
Order By: Relevance
“…Relevant to this, an earlier analysis of maternal BMI in 35 African countries found that after adjusting for early childbearing, early marriage itself was associated with a reduced risk of the mother having low BMI (Efevbera et al, 2019), though the findings from an Indian study were in the opposite direction (Prakash et al, 2011). Research in India has linked earlier menarche with earlier marriage (Raj et al, 2015), and earlier menarche may be associated with higher BMI (Malitha et al, 2020; Żegleń et al, 2020). If women marrying relatively young in our population do indeed have higher BMI, this might also help explain why for some outcomes, those who gave birth at the earliest age (10–14 years) did not always have the worst offspring anthropometric outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Relevant to this, an earlier analysis of maternal BMI in 35 African countries found that after adjusting for early childbearing, early marriage itself was associated with a reduced risk of the mother having low BMI (Efevbera et al, 2019), though the findings from an Indian study were in the opposite direction (Prakash et al, 2011). Research in India has linked earlier menarche with earlier marriage (Raj et al, 2015), and earlier menarche may be associated with higher BMI (Malitha et al, 2020; Żegleń et al, 2020). If women marrying relatively young in our population do indeed have higher BMI, this might also help explain why for some outcomes, those who gave birth at the earliest age (10–14 years) did not always have the worst offspring anthropometric outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Menarche is the most commonly remembered milestone of puberty for most women, and it is often considered the signals of fertility from both social and medical perspectives. Girls experience menarche at different ages but usually it occurs between the ages of 10 and 16 years, and the mean age at menarche varies significantly by geographical region, race, ethnicity, and other characteristic factors, especially nutritional factors [1,2]. Recently, it was found that estradiol is an important factor for the occurrence of kisspeptin expression in GnRH (gonadotropin releasing hormone) neurons in the prepubertal period, and its gradual development provides a GnRH neuron amplification mechanism that is used to facilitate the emergence of pulsatile gonadotropin secretion necessary for puberty onset.…”
Section: Introductionmentioning
confidence: 99%
“…Namely, Tanner stages based on pubic hair scale were estimated [ 25 ] and the date of menarche was obtained retrospectively (year, month, and, if possible, exact day). The recall method has previously been widely used in research, as well as justified as a reliable way to obtain the age of menarche [ 26 , 27 ]. It is a validated method, used for several dozen years all over the world [ 28 , 29 ].…”
Section: Methodsmentioning
confidence: 99%